KESANTUNAN BERBAHASA DALAM TUTURAN FILM MY STUPID BOSS 1 - Wulansafitri, Inayah; Syaifudin, Ahmad (Jurusan Bahasa dan Sastra Indonesia Universitas Negeri Semarang, 2020)
Language politeness is needed to maintain social relations in society. Media is needed to guide the public so they can be polite, one of them is with film. Besides functioning as a movie, it can also be a guide. My Stupid Boss 1 is the third best-selling film in Indonesia with 3 million viewers in 2016. As a film that is still often played on television screens, there may be violations in the film's speech. This study aims to explain the form of obedience and violation of politeness, as well as the implications arising from politeness violations in the movie My Stupid Boss 1. This research approach is a pragmatic approach and a qualitative descriptive approach. The data of this research are in the form of speech fragments which are suspected to have a violation and politeness violation. The source of data in this study is the whole utterance in the film. Data collection techniques using the technique of free and involved in proficiency and note taking techniques. The data analysis method is in the form of a matching method, while the method of presenting the results of data analysis uses the informal method. From 57 data, there are 19 data that obey the politeness principle, 38 data violate politeness principle, and 15 implicatures that appear. From this research it is expected to find meaning in a film that will be useful with references in life.